2020
DOI: 10.22541/au.159837793.30736196
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of Covid-19 Pandemic in Children With Cancer: A Report From Saudi Arabia

Abstract: Background: On January 2020, the WHO declared the novel coronavirus (2019-nCoV) outbreak as a public health emergency of international concern. Due to rapid spread 2019-nCoV, all countries started preventive and precautionary measures to prevent COVID-19 infection spread. These measures limited the population mobility and services provided, which subsequently Impact of on children with cancer and cancer care delivery in the many health centers in Saudi Arabia. Procedure: We did a cross sectional study to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Worldwide, the need to adapt to an uncertain future led to rationing of treatment delivery by suspensions of most pediatric cancer services 13,16–18 . A recent global study reported that 55.8% of children with cancer had modifications in their cancer‐directed therapies during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, the need to adapt to an uncertain future led to rationing of treatment delivery by suspensions of most pediatric cancer services 13,16–18 . A recent global study reported that 55.8% of children with cancer had modifications in their cancer‐directed therapies during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the study revealed that patients with psychological symptoms experienced significant distress. Studies have reported that paediatric patients and youth experience psychosocial issues due to pandemic, impacting their mental health resulting in frequent referrals to psychologist 3,10 …”
Section: Discussionmentioning
confidence: 99%
“…Caregivers experienced anxiety related to children contracting COVID‐19 and hospitals were no longer felt to be a safer place 2 . TheCOVID‐19 pandemic has caused greater impact on the mental health of paediatric patients, requiring professional mental health support 3,4 . Although studies are being published around the pandemic situation in oncology with reference to psychosocial concerns, across different countries, there is scarce resources on psychosocial impact of COVID‐19 pandemic in low‐middle income countries, especially from India.…”
Section: Introductionmentioning
confidence: 99%